Análisis y propuesta de gestión del talento humano admisión y empleo en el ilustre municipio del cantón Saraguro, 2011. - Pineda Hoyos, Liliana del Cisne (2012)
The research process was conducted in the Decentralized Autonomous Government Saraguro, in 2011, aiming to analyze the Human Resource Management (Admission and Employment), the personnel working in that institution. Saraguro Canton is located north of the province of Loja, 64 kilometers from the city of Loja with an altitude of 2755 meters, its total population of 36000 inhabitants, it is distributed in the following parishes Manu Lluzhapa, Selva Alegre, Paraíso de Celén, Urdaneta, San Antonio de Cumbe, El Tablón, San Pablo de Tenta and Sumaypamba. The Decentralized Autonomous Government Saraguro was created on May 27, 1878; by Legislative Decree, which regulates the legal and administrative life of the Canton. The human talent of the Municipality consists of 24 employees with appointments, 53 administrative employees and 56 operating. The systems to investigate were the staff working at the Decentralized Autonomous Government and the people of Canton Saraguro. The sample consisted of two groups: one consisting of 45 staff of the institution, to determine those variables were: organizational culture, training needs, admission and employment, and the second group formed by 378 residents of Canton to determine the variable user satisfaction interviewed. Among the most important organizational culture are: the treatment of employees by managers is excellent (54%) and good (44%), there is teamwork (76%) accepted the suggestions of employees in decision making (60%), knowledge of the mission and vision (56%). Training needs are: 100% of staff surveyed required training, the topics most suggested: leadership (14%), customer service (16%), development of staff (15%), management of human talent (12 %). In admission and employment are: 78% of respondents say they do not apply the appropriate steps for the recruitment, selection, recruitment and induction, there is knowledge of the admission policies and employment (50%). Finally of user satisfaction are: families who know the services provided by the institution (75%), user satisfaction with the care provided by staff (80%), 70% of respondents state that if Self-Government has carried out works to improve services in the parishes of Canton. In addition, staff surveyed 50% know the institutional mission and vision, there is also ignorance about the process of admission and employment. In addition, there are training needs of employees in most, but there is user satisfaction in the care they receive when requesting information, likewise a high percentage of users satisfied with the road works undertaken in the Canton. From the above, I can say that the data and information are of paramount importance to develop proposals for Training, Admission and Employment, to thereby contribute to the development of Human Resource DECENTRALIZED AUTONOMOUS GOVERNMENT SARAGURO.